Peningkatan Hasil Belajar Berbicara Teks Prosedur Melalui Metode Presentasi Power Point Mata Pelajaran Bahasa Inggris Pada Peserta Didik Kelas IX G Semester 1Tahun Pelajaran 2017/2018 SMP Negeri 1 Tugu - Wiwik Sulistyowati (STKIP PGRI Tulungagung, 2018)
Speaking is one of the four language skills that have been taught in English lesson. In this era, speaking ability, especiallyÂ to do public speaking in English is truly substantial in accordance with the era of globalization. In fact, it is known that the students of SMP 1 Tugu still have low ability in public speaking . It is due to some cases such as the lack of self confidence, the limited vocabulary and the feeling of being afraid to make mistake. The application of learning method focus on teacher center oriented is also being the main cause that have to be solved. Therefore, reseacher tries to design the lesson plan providing some challenging activities for students by applying learning method of â€œpresentasi power point â€ . it is intended to enhance the studentsâ€™ achievement in speaking ability of procedure text. The learning design is hoped to be be able to create the meaningful, active, creative and joyful learning atmosphere. For students, the research can increase their abilityÂ to produce procedure text orally. For teacher, it can improve the skill of using various learningÂ methods in class. The research is held based onÂ the research methology of Kemmis that consist of 4 steps, planning, acting, observing and reflecting. This research is designed in two cycles. The studentsâ€™ achivement in cycle 1 shows that minimum score Â hasnâ€™t been achieved yet. The data shows that there are only 21 students passed of 29 , 72,41%. And there is an increasement in the second cycle that is 26 students passed, 89,66%. There is also an increasement of the Â average score, 76,83 in cycle 1 and 81,38 in cycle 2. It means that the students achievement enhance 4,55 %. Thus, it can be inferred that â€˜presentasi power point â€ learning method can enhance the public speaking ability of procedure texts of the first semester students of SMP 1 Tugu, especially class IX G, in the year of 2017 2018.